Reduction of Dioxygen by Radical/B(p‐C6F4X)3 Pairs to Give Isolable Bis(borane)superoxide Compounds. Issue 52 (4th December 2017) - Tao, Xin; Daniliuc, Constantin G.; Janka, Oliver; Pöttgen, Rainer; Knitsch, Robert; Hansen, Michael Ryan; Eckert, Hellmut; Lübbesmeyer, Maximilian; Studer, Armido; Kehr, Gerald; Erker, Gerhard
Abstract: Triplet dioxygen was reduced by TEMPO or trityl radicals in the presence of two molar equivalents of the strong B( p ‐C6 F4 X)3 (X: F or H) boron Lewis acids under mild conditions to give the bis(borane)superoxide systems2 . The sensitive radical anion species were isolated and characterized by methods including X‐ray crystal structure analysis and EPR spectroscopy. Abstract : Super boron : The TEMPO radical reduces triplet dioxygen to the superoxide state in the presence of the strong boron Lewis acid B(C6 F5 )3 . The sensitive radical anion species was isolated and characterized by methods including X‐ray crystal structure analysis and EPR spectroscopy.